Two new genera and six new species of flat mites (Prostigmata: Tenuipalpidae) from Goodeniaceae (Asterales) in Australia - Beard, Jennifer J.; Seeman, Owen D. (Zootaxa, 2025)
We describe two new genera, Goodeniacarus gen. nov. and Inglacarus gen. nov., based on five and one new species, respectively: Goodeniacarus leiperi sp. nov., G. reticulatus sp. nov., G. rosulatus sp. nov., G. uri sp. nov., G. wondul sp. nov.; and Inglacarus jonesi sp. nov. These represent a radiation of flat mites on the primarily Australian plant genus Goodenia (Goodeniaceae). Both new genera show strong affinities with the enigmatic genus Amblypalpus, but we argue that the new genera are a convergently regressive lineage with likely sister groups elsewhere within the Tenuipalpidae. We provide a key to these new species.